STEM and ICT Instructional Worlds: The 3D Experience, The impact on today’s students - William Edward Roberts; Nita Matzen (Journal of Education and Learning (EduLearn), 2013)
In our project, 3D immersive virtual worlds have been implemented in middle schools for instruction in science, technology, engineering, and mathematics (STEM).  The learning and playing, as a curricular tool, has enormous potential for engaging children of all ages in deep learning (Lim, Nonis, and  Hedberg 2006). STEM and ICT Instructional Worlds: The 3D Experience (STEM-ICT 3D) is funded by the National Science Foundation Innovative Technology Experiences for Students and Teachers (ITEST) program. The project is intended to inspire middle school students to pursue studies and careers in science, technology, engineering, and mathematics – particularly information and communication technology (ICT) fields - as well as prepare students with the skills necessary to succeed in STEM education and careers. The project, based on research suggesting student gains in engagement, efficacy, and achievement (Barab, et al, 2005; Educause, 2006; Ketelhut, et al, 2006) proposes to translate the success of an earlier pilot toward a model that can be replicated in other middle schools over time.